Effect of Shi-Zhen-An-Shen herbal formula granule in the treatment of young people at ultra-high risk for psychosis: a pilot study - Zhu, Hong; Ning, Yanzhe; Zheng, Sisi; Feng, Sitong; Dong, Linrui; Jia, Hongxiao (Frontiers in Psychiatry, 2023)
Introduction To date, there is no conclusive evidence for early interventions on ultra-high risk (UHR) for psychosis. The Chinese herbal medicine is confirmed to be beneficial in improving psychiatric symptoms and cognitive impairments for schizophrenia patients. However, the effect of Chinese herbal medicine on treating UHR patients remains unknown. Methods Eighty UHR patients were recruited from the outpatient department. They were randomly assigned to receive either Shi-Zhen-An-Shen herbal formula granule (SZAS-HFG) combined with aripiprazole placebo or aripiprazole combined with SZAS-HFG placebo for a 12-week treatment. The psychiatric symptoms were assessed using the Structured Interview for Prodromal Syndromes (SIPS). The Trail Making Test (TMT), Brief Visuospatial Memory Test (BVMT), Hopkins Verbal Learning Test (HVLT), and Continuous Performance Test (CPT) were used to assess cognitive functions. we also employed the Global Assessment of Functioning (GAF) to evaluate social functioning. The linear mixed-effects models were performed to detect the difference in effectiveness between the two groups. Results After 12-week treatment, both groups showed significant effects of time on SIPS, TMT, HVLT, BVMT and GAF. There was a significant effect of group only on CPT. Moreover, we also found a significant interaction effect on GAF. Conclusion SZAS-HFG effectively alleviates psychosis symptoms, and improves cognitive impairments and social functioning impairment. Notably, SZAS-HFG is more effective than aripiprazole in treating the attentional impairment.